Effect of Rim Angle to the Flux Distribution Diameter in Solar Parabolic Dish Collector - Billy, Anak Sup; Mohd Farid, Zainudin; Tanti Zanariah, Shamshir Ali; R. A., Bakar; Gan, Leong Ming (Elsevier Ltd, 2015)
Solar energy application through parabolic dish collector is promising finite green energy such as electric generation. A study of solar parabolic dish collector had been carried out on the geometry and flux distribution at focal region. Rim angle is an important parameter to determine the imaging and non-imaging diameter of the flux radiation. The imaging and non-imaging geometry were simulated using the ray tracing simulation and 2D computer aided drawing. The flux distribution was then tabulated on coordinated graph to obtain the diameter. The imaging diameters are in the ranges of 17 mm to 286 mm while the non-imaging diameter values are in the ranges of 23 mm to 345 mm. Reflex rim angle yields small imaging and non-imaging diameters which values are 37 mm and 53 mm respectively. An acute rim angle yields larger imaging and non-imaging diameter. It shows that the optimum parameter of the parabolic dish is important to achieve high intensity of focus point.